Analysis of Campus WiFi Network Quality Based on Quality of Experience (QoE) - Nurhidayatullah, Muhammad; Nabilah, Ersya (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2025)
This study aims to evaluate the perceptions of students at Universitas Negeri Makassar regarding the quality of the campus WiFi network services using a Quality of Experience (QoE) approach based on the Mean Opinion Score (MOS) scale. A descriptive quantitative method was applied by distributing an online questionnaire to 100 active respondents. The results show that all indicators related to connectivity, stability and speed, as well as convenience and satisfaction in usage obtained average MOS scores above 4.50 and are categorized as very good. These findings indicate that the campus WiFi service has been able to meet students’ academic needs and provide a satisfactory user experience.